Higher water temperature leads to precocious maturation of western rock lobsters (Panulirus cygnus), but are things that simple? - Melville-Smith, Roy; de Lestang, S.; Johnston, D.J. (Marine Biological Association of India, 2010)
During a rock lobster post-puerulus grow out project, western rock lobsters from three different cohorts (post-puerulus, year-1 and year-2) were held for 12 months under two temperature regimes (ambient and 23oC) and two feed delivery treatments (the same ration of pelleted diet fed once nightly and in the alternate treatment, thrice nightly). At the end of the trial, 43% of females from the largest cohort (2-year post settlement) in the 23oC treatment, had ovigerous setae. However, none of the animals held at ambient temperatures showed signs of maturity. Feed delivery did not influence the presence or absence of ovigerous setae. Male maturity responded to elevated temperature in the same way as for females, as indicated by merus/carapace length ratios. The response of female size at maturity to 23oC was compared to a similar trial in the 1970s in which 2-year post settlement animals wereheld at 25oC. Maturity of females in that study was one year later than in the trial reported here, indicating that there may have been a decrease in age at maturity since the 1970s. The conclusion from this and research on other rock lobster species, is that size/age at maturity is likely to be a complex response to a range of contributing factors of which temperature is an important one.